2012
DOI: 10.7150/ijbs.3805
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ Signaling and Cardiovascular Diseases

Abstract: Transforming growth factor β (TGFβ) family members are involved in a wide range of diverse functions and play key roles in embryogenesis, development and tissue homeostasis. Perturbation of TGFβ signaling may lead to vascular and other diseases. In vitro studies have provided evidence that TGFβ family members have a wide range of diverse effects on vascular cells, which are highly dependent on cellular context. Consistent with these observations genetic studies in mice and humans showed that TGFβ family member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 233 publications
1
87
0
2
Order By: Relevance
“…40 TGF-β signaling operates as a rheostat that controls EC differentiation having both inhibitory and stimulating effects. 53 EC sprouting has been explained by a model in which TGF-β synergizes with VEGF and Notch to drive migration, partly through induction of ID1, required for EC migration. 54 The link between the p53 family members and TGF-β signaling in somatic cells has been previously established and it has been suggested, but never addressed, that the p53 homologs might interact with TGF-β in development.…”
Section: Discussionmentioning
confidence: 99%
“…40 TGF-β signaling operates as a rheostat that controls EC differentiation having both inhibitory and stimulating effects. 53 EC sprouting has been explained by a model in which TGF-β synergizes with VEGF and Notch to drive migration, partly through induction of ID1, required for EC migration. 54 The link between the p53 family members and TGF-β signaling in somatic cells has been previously established and it has been suggested, but never addressed, that the p53 homologs might interact with TGF-β in development.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β belongs to a growth factor super-family which consists of a highly evolutionary conserved group of secreted cytokines (6). The TGF-β family consists of TGF-β, activins, bone morphogenetic proteins (BMPs), nodals, inhibins and antimullerian hormone (AMH).…”
Section: Introductionmentioning
confidence: 99%
“…The cell cycle pathways in 2D are dominated with gene sets which are involved in regulating mesodermal differentiation. It has been reported that ectodermal differentiation inhibits the mesodermal differentiation mediated by TGF-β signaling pathway [9,29,30]. Therefore, it may be interpreted that the cells in 2D are still in the transitional stage between ectodermal and mesodermal differentiation where the TGF-β signaling molecules are still active.…”
Section: Discussionmentioning
confidence: 99%